Karakteristik Dewan terhadap Struktur Modal dan Dampaknya terhadap Nilai Perusahaan Manufaktur Syariah - Aldiansyah, Aldiansyah; Mai, M. Umar; Marwansyah, Marwansyah (Jurnal Manajemen Bisnis dan Keuangan, 2023)
Capital structure and firm value have long been developed by a large number of researchers, but no agreement has been reached. One of the keys to optimizing organizational resources is board diversity. Having a well-diversified board influences company performance. An independent and effective board increases the quality and quantity of information provided by insiders to the public and therefore reduces adverse selection costs. This study aims to determine the effect of board characteristics on the capital structure of Islamic manufacturing companies in Indonesia and their impact on firm value. The analytical method used is multiple linear regression using panel data. The independent variables analyzed in this study are the number of directors, the number of commissioners, the number of independent commissioners, and the number of female directors, while the dependent variable is leverage as measured using the debt to asset ratio, which is then tested again on firm value as the dependent variable. as measured using Tobin's Q. The research results show that the number of the Board of Directors has no effect on the capital structure, the number of the Board of commissioners has a positive and significant effect on the capital structure, the number of independent commissioners has an effect positively and significantly to capital structure, the number of female board of directors has a negative and significant effect on capital structure, and capital structure has a positive effect on firm value.